Melatonin and verteporfin synergistically suppress the growth and stemness of head and neck squamous cell carcinoma through the regulation of mitochondrial dynamics - Shin, Ye Young; Seo, Yoojin; Oh, Su‐Jeong; Ahn, Ji‐Su; Song, Min‐hye; Kang, Min‐Jung; Oh, Jung‐Min; Lee, Dongjun; Kim, Yun Hak; Sung, Eui‐Suk; Kim, Hyung‐Sik (Journal of pineal research, 2022)
The prevalence of head and neck squamous cell carcinoma (HNSCC) has continued to rise for decades. However, drug resistance to chemotherapeutics and relapse, mediated by cancer stem cells (CSCs), remains a significant impediment in clinical oncology to achieve successful treatment. Therefore, we focused on analyzing CSCs in HNSCC and demonstrated the effect of melatonin (Mel) and verteporfin (VP) on SCC‐25 cells. HNSCC CSCs were enriched in the reactive oxygen species‐low state and in sphere‐forming cultures. Combination treatment with Mel and VP decreased HNSCC viability and increased apoptosis without causing significant damage to normal cells. Sphere‐forming ability and stem cell population were reduced by co‐treatment with Mel and VP, while mitochondrial ROS level was increased by the treatment. Furthermore, the expression of mitophagy markers, parkin and PINK1, was significantly decreased in the co‐treated cells. Mel and VP induced mitochondrial depolarization and inhibited mitochondrial function. Parkin/TOM20 was localized near the nucleus and formed clusters of mitochondria in the cells after treatment. Moreover, Mel and VP downregulated the expression of markers involved in epithelial‐mesenchymal transition and metastasis. The migration capacity of cells was significantly decreased by co‐treatment with Mel and VP, accompanied by the down‐regulation of MMP‐2 and MMP‐9 expression. Taken together, these results indicate that co‐treatment with Mel and VP induces mitochondrial dysfunction, resulting in the apoptosis of CSCs. Mel and VP could thus be further investigated as potential therapies for HNSCC through their action on CSCs.